1990
DOI: 10.1111/j.1530-0277.1990.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Perception and Memory in Alcoholism and Aging

Abstract: The ability to identify and recognize emotional materials was studied in 10 male alcoholic Korsakoff patients, 27 male non-Korsakoff alcoholics, and 31 male nonalcoholic controls, across a wide age range (23 to 77 years). Stimulus materials were presented in two sensory modalities; the materials were photographs of faces expressing one of four emotions (happy, sad, angry, or neutral), and recordings of sentences with emotional intonations or semantic meanings expressing the same four emotions. Results of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 16 publications
6
71
0
2
Order By: Relevance
“…In rats discriminating between reward-predicting and non-predicting cues, single neurons of the VPM mediate the acquired affective significance of sensory stimuli (termed 'retrospective coding') and predict the value of upcoming reward ('prospective coding') (Komura et al, 2001). It is noteworthy that in humans, VTA opioid receptors, reward and fos protein expression V David et al diencephalic amnesia (ie Korsakoff syndrome) result in a difficulty in assessing the affective component of memories and contexts (Oscar-Berman et al, 1990;Snitz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In rats discriminating between reward-predicting and non-predicting cues, single neurons of the VPM mediate the acquired affective significance of sensory stimuli (termed 'retrospective coding') and predict the value of upcoming reward ('prospective coding') (Komura et al, 2001). It is noteworthy that in humans, VTA opioid receptors, reward and fos protein expression V David et al diencephalic amnesia (ie Korsakoff syndrome) result in a difficulty in assessing the affective component of memories and contexts (Oscar-Berman et al, 1990;Snitz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have investigated how the ability to identify vocal expressions of emotion fares with age. Some studies have compared overall recognition of auditory expressions in young versus older adults, and have found worse recognition in older adults (usually defined as 60þ years), but have not isolated individual emotions (Kiss & Ennis, 2001;Mitchell, 2007;Orbelo, Grim, Talbott, & Ross, 2005;Orbelo, Testa, & Ross, 2003;Oscar-Berman, Hancock, Mildworf, Hutner, & Altman Weber, 1990;Raithel & HielscherFastabend, 2004). Other authors have isolated individual emotions.…”
mentioning
confidence: 99%
“…In older adults (Albert & Knoefel, 1994;Jenike, 1988), as in individuals with alcoholism (Grant & Harford, 1995), affective changes frequently occur, with depression and apathy being common symptoms. Abnormalities in the ability to recognize emotional facial expressions (Calder et al, 2003;Oscar-Berman et al, 1990), and differential activation patterns in response to these expressions (Iidaka et al, 2002), also have been reported in older adults. Thus, an accumulation of evidence appears to suggest the possible involvement of frontal and limbic brain systems in the abnormal processing of facial affect that is seen in alcoholism, as well as in aging.…”
mentioning
confidence: 99%